RECONSTRUCTING MADRASAH IDENTITY THROUGH AL-GHAZALI’S EPISTEMOLOGY IN CONTEMPORARY EDUCATION - Arbainsyah, Arbainsyah; Hamdanah, Hamdanah; Wahidin, Wahidin (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
Background: Contemporary’s trend in education indoensian has shifted orientation of madrasah, caused disapperance its humanistic-religious character, neglecting of spiritual aspect in practice. On the contrary, empirical-pragmatice inhibited madrasah to adapt with contempoary education dynamics, such a charactes by al-Ghazali, who stated that ultimate reality can not gained by rational-empiric without involving  spiritual intuition. Porpuse of the study:  This study proposes a unique framework for integrating Al-Ghazali’s epistemology into madrasah education, aiming to harmonize divine revelation, reason, and spiritual intuition in shaping contemporary educational practices. Method: This study employed a library research method using secondary sources, such as scientific texts, journal articles, and classical books, with in-depth information gathering to identify impact of the relationship between scriptural revelation (naql), reason(aql), and intuition in Al-Ghazali’s thought. Result: Al-Ghazali posited that reason(aql) and empirical experience are insufficient for realization of the ultimate truth without the incorporation of spiritual experience (irfani), gained through creation enviroment namely riyadhah (spiritual training), al-Ghazali stated character was a soul spontaneity, Conclusion:  thus, it can be concluded that the reconstruction of the madrasah's epistemology has a potential to harmonize the dimensions of scriptural revelation (naql), reason (aql), and intuition (irfani). it is crucial for madrasahs to adapt to contemporary era while maintaining their identity as formal Islamic education through a holistic approach, ensuring that students are intellectually competent as well as morally and spiritually grounded.